Bibliometric analysis of published documents on entrepreneurship in basic sciences (Physics, Chemistry, Biology) - Deveci, İsa (Journal of Turkish Science Education, 2024)
In recent years, efforts to transform scientific information produced in basic sciences into technology to facilitate life in daily life have been increasing. In this sense, the perspective of entrepreneurship gains importance in basic sciences. This study aims analze documents published on entrepreneurship in basic sciences (physics, chemistry, biology) using a bibliometric review. For this aim, the bibliometric analysis method based on the systematic literature review approach was used. Systematic review was carried out in the WoS database. A total of 428 documents on entrepreneurship in basic sciences in the WoS were retrieved. The bibliometric analysis results were presented under two main categories as descriptive (numbers of documents according to year, author, country, organization, source, research area, WoS category area) and evaluative results (co-occurrence, co-authorship, citation analysis). Descriptive results were displayed with frequency values, and evaluative results were displayed using VOSviewer visualization software. As a result, it was determined that there is a important increase in the number of documents towards 2020. In addition, it was determined that the most productive, influential, and collaborative author is Jardım-Goncalves R, the most productive country is the USA, the most productive journal is Journal of Technology Transfer, and the most productive organization is Old Dominion University. Moreover, it has been determined that the most influential area in terms of research area is “business economics” and the most keyword co-occurences are “entrepreneurship”, “design science” and “academic entrepreneurship”.